2021
DOI: 10.1088/1751-8121/ac1f3f
|View full text |Cite
|
Sign up to set email alerts
|

Shor–Movassagh chain leads to unusual integrable model

Abstract: The ground state of the Shor–Movassagh chain can be analytically described by the Motzkin paths. There is no analytical description of the excited states. The model is not solvable. We prove the integrability of the model without interacting part in this paper (free Shor–Movassagh). The Lax pair for the free Shor–Movassagh open chain is explicitly constructed. We further obtain the boundary K-matrices compatible with the integrability of the model on the open interval. Our construction provides a direct demons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This work was then generalized by Movassagh and Shor to any integer spin s ≥ 1 in [MS16] and called s−colored Motzkin quantum spin chain, where each color represents a spin value s. In particular, it was proved that for any number of colors s > 1 the model exhibits tremendous amount of entanglement in its ground state which was not previously believed possible for ground states of physical quantum spin chains. Later, Korepin et al found that the s−colored Motzkin chain is an unusual integrable model [TSHK21]. The frustration-freeness along with the combinatorial nature of the ground state structure allows one to map these quantum models to classical Markov processes in classical probability theory for analyzing the entanglement entropy of the ground state and the gap above the ground state.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…This work was then generalized by Movassagh and Shor to any integer spin s ≥ 1 in [MS16] and called s−colored Motzkin quantum spin chain, where each color represents a spin value s. In particular, it was proved that for any number of colors s > 1 the model exhibits tremendous amount of entanglement in its ground state which was not previously believed possible for ground states of physical quantum spin chains. Later, Korepin et al found that the s−colored Motzkin chain is an unusual integrable model [TSHK21]. The frustration-freeness along with the combinatorial nature of the ground state structure allows one to map these quantum models to classical Markov processes in classical probability theory for analyzing the entanglement entropy of the ground state and the gap above the ground state.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…We studied the free Motzkin chain with periodic boundary conditions. Based on intrinsic properties of the R-matrix, we derive the functional relations (27) of the transfer matrix. These relations, together with the asymptotic behavior (30), allow us to construct a generalized T − Q relation (31) for the eigenvalues of the transfer matrix and the associated Bethe equations (33).…”
Section: Discussionmentioning
confidence: 99%
“…Let ã and d represent the coefficients before a(λ) and d(λ) terms, respectively. Based on the identities (27) and the asymptotic behavior ( 24) and ( 30), these coefficients…”
Section: Structure Of Operator ô and Its Eigenvaluesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the RE scheme and the Lax pair formulation can demonstrate the integrability of the model. There is one special case where only the Lax pair formulation works for the model without crossing unitarity [15], while the RE scheme does not. When solving the RE, one has to take into account the spectral parameter and the crossing parameter.…”
Section: Discussionmentioning
confidence: 99%